2018
DOI: 10.1039/c7ra13481a
|View full text |Cite
|
Sign up to set email alerts
|

Radical-initiated alkene hydroauration as a route to gold(iii) alkyls: an experimental and computational study

Abstract: Gold(iii) hydrides undergo radical-induced insertion reactions with alkenes via gold(ii) intermediates. The success of the reaction depends on the degree of spin delocalisation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 25 publications
1
14
0
Order By: Relevance
“…The calculations also showed the increase in radical stability in the order R1 < R2 ≪ R3 (Scheme 82), which explains the facile insertion of allenes. 386 Whereas the previously described bimolecular reaction pathway via Au(II) radicals led to 1,2-insertion products, the hydroauration of arylisocyanides is a 1,1-insertion process. Fernandez-Cestau et al reported the first example of such an insertion, to give the gold(III) iminoformyl complex (C^N^C)-Au−CHNAr (223).…”
Section: Insertions Into Gold−carbon Bondsmentioning
confidence: 99%
See 1 more Smart Citation
“…The calculations also showed the increase in radical stability in the order R1 < R2 ≪ R3 (Scheme 82), which explains the facile insertion of allenes. 386 Whereas the previously described bimolecular reaction pathway via Au(II) radicals led to 1,2-insertion products, the hydroauration of arylisocyanides is a 1,1-insertion process. Fernandez-Cestau et al reported the first example of such an insertion, to give the gold(III) iminoformyl complex (C^N^C)-Au−CHNAr (223).…”
Section: Insertions Into Gold−carbon Bondsmentioning
confidence: 99%
“…Calculations showed that this behavior was a function of the exergonic or endergonic character of alkyl radical formation, driven by spin delocalization over the unsaturated substituents. The calculations also showed the increase in radical stability in the order R1 < R2 ≪ R3 (Scheme ), which explains the facile insertion of allenes …”
Section: Catalysis-relevant Reaction Stepsmentioning
confidence: 99%
“…Additionally, these in situ generated gold(II) radicals react with 1-alkenes leading to gold(III) alkyl complexes. 87 The T-shaped Au(III)-H complex 26 presents a covalent Au−H bond, which does not react with excess of various acids, but addition of NaH produced the regeneration of the starting material and formation of H 2 (g) after 3 days at room temperature (Scheme 24). This result corroborates the protic and not hydridic character of the complex.…”
Section: Gold Hydride Complexesmentioning
confidence: 99%
“…The reactivity of gold(III) hydrides reflects this; whereas B can be deprotonated only by very strong bases, 7 complexes of type A undergo homolytic Au–H bond cleavage and insertion reactions with alkenes and alkynes via bimolecular pathways involving (C^N^C)Au II radical intermediates. 6 , 10 …”
Section: Introductionmentioning
confidence: 99%